Neighbourhood-level air pollution and greenspace and inflammation in adults. (July 2019) - Midouhas, Emily; Kokosi, Theodora; Flouri, Eirini
Abstract: Inflammation has been proposed as a pathway from adverse physical environments to poor physical and mental health. We estimated longitudinal associations of neighbourhood-level air pollution and greenspace with individual-level inflammation (measured with C-reactive protein and fibrinogen), using data from over 8000 adults living in England and Wales who participated in Understanding Society. Using linear regression, we found that neighbourhood-level nitrogen dioxide predicted later levels of fibrinogen, but not C-reactive protein. Area air pollution, but not area greenery, appears to predict inflammation, even after accounting for social deprivation in the area. Highlights: Inflammation is a key proposed pathway from the physical environment to health. Neighbourhood air pollution and greenspace effects on inflammation were tested. Nitrogen dioxide concentrations predicted later elevated levels of fibrinogen. The amount of greenspace was unrelated to inflammation markers.